2003
DOI: 10.1111/j.1750-3639.2003.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antioxidant Enzymes in Astrocytic Brain Tumors

Abstract: We studied the expression of antioxidant enzymes (AOEs) and related proteins manganese superoxide dismutase (MnSOD), thioredoxin (Trx), thioredoxin reductase (TrxR), and the catalytic (GLCL‐c) and regulatory (GLCL‐r) subunits of glutamate cysteine ligase (γ‐glutamylcysteinesynthetase) in 433 astrocytomas. Expression of MnSOD was found in 91%, Trx in 46%, TrxR in 66%, GLCL‐c 73% and GLCL‐r in 89% of the cases. Diffuse astro‐cytomas showed more intense staining for Trx (p= 0.002), TrxR (p=0.004), GLCL‐c (p=0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 42 publications
(46 reference statements)
2
42
0
Order By: Relevance
“…SOD2 in carcinogenesis has been widely studied but remains ambiguous. As one of the major antioxidant enzymes, it was proved to inhibit growth of tumor cells in cultured cancer cells and experimental animal models (33)(34)(35)(36), but was upregulated in various solid tumors, including lung cancer (37)(38)(39)(40)(41)(42). Consistent with previous studies that found the increased SOD2 in lung tumors and in the sera of lung SCC patients (41,42), SOD2 was observed to be up-regulated in lung SCC tumors compared with corresponding normal lung tissues in our study.…”
Section: Discussionmentioning
confidence: 99%
“…SOD2 in carcinogenesis has been widely studied but remains ambiguous. As one of the major antioxidant enzymes, it was proved to inhibit growth of tumor cells in cultured cancer cells and experimental animal models (33)(34)(35)(36), but was upregulated in various solid tumors, including lung cancer (37)(38)(39)(40)(41)(42). Consistent with previous studies that found the increased SOD2 in lung tumors and in the sera of lung SCC patients (41,42), SOD2 was observed to be up-regulated in lung SCC tumors compared with corresponding normal lung tissues in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by in vivo analyses that correlate SOD2 overexpression with worse prognosis in solid tumors. Several reports have shown increased SOD2 levels in many malignancies, including lung [20,33], colorectal [16,36], gastric and esophageal [13,17], brain [9], oral [22] and skin carcinomas [32], often associated with metastasis and poor prognosis. In contrast, SOD2 reduction was also observed in prostatic carcinomas when compared to normal tissues [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Not only does downregulation of SOD-1 expression increases sensitivity of tumor cells to the cytotoxic agents (28) but the anticancer activity of some flavonoids has also been attributed to their ability to inhibit thioredoxin reductase (10). Importantly, SOD and TRX have been implicated in the pathogenesis of astrocytomas (40). Our findings that siRNA-mediated down-regulation of SOD-1 and TRX-1 in gliomas increases ROS generation and enhances sensitivity to kaempferolinduced apoptosis are consistent with previous reports that inhibition of SOD (7) and TRX (29) enhances sensitivity of tumor cells to ROS-generating anticancer agents.…”
Section: Discussionmentioning
confidence: 99%